2018
DOI: 10.1016/j.mtcomm.2018.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of nanomaterials: A crucial step in biosensor fabrication

Abstract:  An easy, stable, and reproducible nanomaterial deposition/growth method is crucial for the realization of fabricated biosensor devices' performance, such as device stability, and reproducibility, as well as other sensing properties.  Key challenges for optimum deposition include stability, reproducibility, repeatability, and the ability of deposited nanomaterials to address these challenges is critiqued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(102 citation statements)
references
References 433 publications
(302 reference statements)
0
96
0
6
Order By: Relevance
“…A H 2 S gas sensor was developed with SnO 2 nanowires. 7 It was reported that nanomaterials deposition onto a conductive electrode was a crucial step for obtaining improved performance. Oxidation of Cu to CuO was well-controlled to form CuO@SnO 2 p-n heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A H 2 S gas sensor was developed with SnO 2 nanowires. 7 It was reported that nanomaterials deposition onto a conductive electrode was a crucial step for obtaining improved performance. Oxidation of Cu to CuO was well-controlled to form CuO@SnO 2 p-n heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…The review article reported various metal oxide nanomaterials and their applications to biosensors. 7 It was reported that nanomaterials deposition onto a conductive electrode was a crucial step for obtaining improved performance. An easy, stable, and reproducible nanomaterial deposition method was indispensable to biosensor devices.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, and graphene-like materials can be used for a multitude of sensing applications. While it has been documented that neither material alone is the most efficient platform for direct detection of glucose or detection of H 2 O 2 [6], they remain important base components or scaffolds for metal-based catalysts in electrochemical sensor applications [10][11][12]. As such, many graphene-or carbon-based electrochemical sensors have been evaluated using classical benchmark testing of H 2 O 2 oxidation and detection of glucose (typically via the breakdown of glucose) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Specific enzymes for the detection of phenols (e.g., tyrosinase, laccase or peroxidase) or sugars (e.g., glucose oxidase or fructose dehydrogenase) among others, have been incorporated into bioelectronic tongues [44,106,107,109,[119][120][121][122]. temperature and is carried out using three electrodes dipped into the solution at a potential (or current, depending on the method used) that is applied to polymerize the monomer and/or reduce metal ions in the simultaneous preparation of polymer composites with metal nanoparticles [136].…”
Section: Principles Of Detection: Electrochemical Methodsmentioning
confidence: 99%
“…Printing-based methods have been used to deposit materials onto rigid and flexible substrates to make devices on a large-scale at low cost. One advantage of these methods is that they allow nanomaterials to be desposited directly onto predesigned patterns [136].…”
Section: Sensor and Biosensor Constructionmentioning
confidence: 99%